Enhancing Clinical Relevance of GLIM Criteria in Acute Pancreatitis: A Call for Integrated Practice [Response to Letter] - Fu H (International Journal of General Medicine)
Hao Fu Nutrition Department, Affiliated Hospital of Chengde Medical University, Chengde, People’s Republic of ChinaCorrespondence: Hao Fu, Email williamfu85@163.com